Spectroscopy of atomic and molecular defects in solid ⁴He using optical, microwave, radio frequency, magnetic and electric fields (Review Article) - Moroshkin, P.; Hofer, A.; Ulzega, S.; Weis, A. (Физика низких температур, 2006)
A little more than a decade ago our team extended the field of defect spectroscopy in
cryocrystals to solid ⁴He matrices, in both their body-centered cubic (bcc) and hexagonally
close-packed (hcp) configurations. In this review paper we survey our pioneering activities in the
field and compare our results to those obtained in the related fields of doped superfluid helium and
doped helium nanodroplets, domains developed in parallel to our own efforts. We present experimental
details of the sample preparation and the different spectroscopic techniques. Experimental
results of purely optical spectroscopic studies in atoms, exciplexes, and dimers and their interpretation
in terms of the so-called bubble model will be discussed. A large part of the paper is devoted
to optically detected magnetic resonance, ODMR, processes in alkali atoms. The quantum nature
of the helium matrix and the highly isotropic shape of the local trapping sites in the bcc phase
make solid helium crystals ideal matrices for high resolution spin physics experiments. We have investigated
the matrix effects on both Zeeman and hyperfine magnetic resonance transitions and
used ODMR to measure the forbidden electric tensor polarizability in the ground state of cesium.
Several unexpected changes of the optical and spin properties during the bcc—hcp phase transition
can be explained in terms of small bubble deformations.